2000
DOI: 10.1046/j.1365-2222.2000.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Airborne endotoxin exposure and the development of airway antigen‐specific allergic responses

Abstract: These data show that airborne endotoxin exposure could potentiate allergen-specific airway inflammation. The results should have potential implications for understanding the development of allergen-induced airway allergic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
45
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 33 publications
4
45
0
Order By: Relevance
“…The findings of this study are consistent with work by others that found that administration of LPS, a well-characterized TLR4 activator, resulted in enhanced Ag-specific IgE production and airway eosinophilia (19,44) and that these effects were mediated by up-regulation of CD86 on APCs (44). This suggests that a TLR4 ligand, such as LPS derived from endogenous bacterial flora, may influence dendritic cell maturation in vivo, compromising the ability of these cells to up-regulation of costimulatory molecule expression and to direct Th2 immune responses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this study are consistent with work by others that found that administration of LPS, a well-characterized TLR4 activator, resulted in enhanced Ag-specific IgE production and airway eosinophilia (19,44) and that these effects were mediated by up-regulation of CD86 on APCs (44). This suggests that a TLR4 ligand, such as LPS derived from endogenous bacterial flora, may influence dendritic cell maturation in vivo, compromising the ability of these cells to up-regulation of costimulatory molecule expression and to direct Th2 immune responses.…”
Section: Discussionsupporting
confidence: 92%
“…This interpretation is in agreement with some murine studies in which LPS administration increased allergen-specific IgE production and pulmonary eosinophilia (19,44), but not another, in which genetic deficiency of LPS-binding protein, a molecule that serves as a chaperone for LPS binding to CD14, had Th2 responses similar to those of WT mice (53). Human epidemiological studies examining the role of LPS exposure in the risk of development of asthma have also been conflicting (22,23).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, active protease is not required for airway Ag presentation, only allergic responses to Ag. Although protease and amylase activities were common to all of our allergens and numerous additional molecules (32,33) potentially relevant to allergic disease are doubtless present in the A. oryzae allergen, only protease was required for disease. Thus, while many microbial factors may contribute to expression of some features of experimental allergic disease, our data strongly suggest that only protease is necessary for the asthma phenotype.…”
Section: Discussionmentioning
confidence: 95%
“…Other differences include the route of challenge, which can be by intratracheal instillation, oropharyngeal application, or inhalation of OVA-based aerosol. In view of these procedural differences among various laboratories, it is perhaps not surprising that endotoxin has been reported to both increase (12)(13)(14)(15) and decrease (16 -22) the intensity of allergic responses, and a comprehensive understanding of the mechanisms by which endotoxin affects allergic responses has remained elusive.…”
mentioning
confidence: 99%